Parenteral Nutrition Combined with Enteral Nutrition for Severe Acute Pancreatitis. (11th December 2012) - Singh, Akanand; Chen, Ming; Li, Tao; Yang, Xiao-Li; Li, Jin-Zheng; Gong, Jian-Ping
Abstract : Background and Aims . Nutritional support in severe acute pancreatitis (SAP) is controversial concerning the merits of enteral or parenteral nutrition in the management of patients with severe acute pancreatitis. Here, we assess the therapeutic efficacy of gradually combined treatment of parenteral nutrition (PN) with enteral nutrition (EN) for SAP. Methods . The clinical data of 130 cases of SAP were analyzed retrospectively. Of them, 59 cases were treated by general method of nutritional support (Group I) and the other 71 cases were treated by PN gradually combined with EN (Group II). Results . The APACHE II score and the level of IL-6 in Group II were significantly lower than Group I ( P < 0.05 ) . Complications, mortality, mean hospital stay, and the cost of hospitalization in Group II were 39.4 percent, 12.7 percent, 32 ± 9 days, and 30869.4 ± 12794.6 Chinese Yuan, respectively, which were significantly lower than those in Group I. The cure rate of Group II was 81.7 percent which is obviously higher than that of 59.3% in Group I ( P < 0.05 ) . Conclusions . This study indicates that the combination of PN with EN not only can improve the natural history of pancreatitis but also can reduce the incidence of complication and mortality.